Surveys of Arboviruses Vectors in Four Cities Stretching Along a Railway Transect of Burkina Faso: Risk Transmission and Insecticide Susceptibility Status of Potential Vectors - Ouattara, Lissy Parfait Eric; Sangaré, Ibrahim; Namountougou, Moussa; Hien, Aristide; Ouari, Ali; Soma, Dieudonné Diloma; Kassié, Daouda; Diabaté, Abdoulaye; Gnankiné, Olivier; Bonnet, Emmanuel; Ridde, Valéry; Akré, Maurice Adja; et al. (Frontiers in Veterinary Science, 2019)
Background: A severe outbreak of dengue occurred in Burkina Faso in 2016, with the main cases reported in Ouagadougou, which highlights the necessity to implement vector surveillance system. This study aims to estimate the risk of arboviruses transmission and the insecticide susceptibility status of potential vectors in four sites in Burkina Faso. Methods: From June to September 2016, house-to-house cross sectional entomological surveys were performed in four cities stretching along a southwest-to-northeast railway transect. The household surveys analyzed the presence of Aedes spp larvae in containers holding water and the World Health Organization (WHO) larval abundance indices were estimated. WHO tube assays was used to evaluate the insecticide susceptibility within Aedes populations from these localities. Results: A total of 31,378 mosquitoes’ larvae were collected from 1,330 containers holding water. Aedes spp was the most abundant (95.19%) followed by Culex spp (4.75%). Aedes aegypti a key vector of arboviruses (ARBOV) in West Africa was the major Aedes species found (98.60%). The relative larval indices house index, container and Breteau indexes were high, up to 70, 35 and 10 respectively. Ae. aegypti tended to breed mainly in discarded tires and terracotta jars. Except in Banfora the western city, Ae. aegypti populations were resistant to deltamethrin 0.05% with low mortality rate under 20% in Ouagadougou whereas they were fully susceptible to malathion 5% whatever the site. Intermediate resistance was observed in the four sites with bendiocarb 0.1% with mortality rates varying between 78-94%. Conclusions: Our study provided basic information on entomological indices that can help to monitor the risks of ARBOV epidemics in the main cities along the railway in Burkina Faso. In these cities, all larval indices exceeded the risk level of ARBOV outbreak. Aedes aegypti the main species collected was resistant to deltamethrin and bendiocarb. The monitoring of insecticide resistance is also important to be integrated to the vector surveillance system in Burkina Faso.